2013
DOI: 10.5665/sleep.3058
|View full text |Cite
|
Sign up to set email alerts
|

Association between Total Sleep Duration and Suicidal Ideation among the Korean General Adult Population

Abstract: The sleep duration/suicidal ideation relationship is U-shaped in the Korean adult population. Self-reported habitual sleep duration may be a useful behavioral indicator for both individual and societal suicidal ideation risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 47 publications
(50 reference statements)
7
40
2
1
Order By: Relevance
“…In the present study, the percentage of individuals who had suicidal ideation was higher among stroke survivors who slept <5 h, but lower among stroke survivors who slept ≥9 h. Such results point to the importance of stroke survivors receiving adequate sleep duration. Even after adjusting for significant covariates, the final model confirmed that stroke survivors who slept ≤5 h were 2.71‐fold more at risk of suicidal ideation than those who slept ≥9 h. This result is consistent with previous studies of the general adult population, adolescents and college students . Because suicidal ideation is more common among stroke survivors than the general adult population, our analysis of sleep duration and suicidal ideation among stroke survivors is highly meaningful.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the percentage of individuals who had suicidal ideation was higher among stroke survivors who slept <5 h, but lower among stroke survivors who slept ≥9 h. Such results point to the importance of stroke survivors receiving adequate sleep duration. Even after adjusting for significant covariates, the final model confirmed that stroke survivors who slept ≤5 h were 2.71‐fold more at risk of suicidal ideation than those who slept ≥9 h. This result is consistent with previous studies of the general adult population, adolescents and college students . Because suicidal ideation is more common among stroke survivors than the general adult population, our analysis of sleep duration and suicidal ideation among stroke survivors is highly meaningful.…”
Section: Discussionsupporting
confidence: 88%
“…The average working time of adult Korean women is 217 min per day, whereas American women work an average of 179 min per day, and German women work an average of 124 min per day. 31 These findings indicate that Korean adults work longer hours than adults in comparable nations and are therefore more likely to be sleep deprived.…”
Section: Discussionmentioning
confidence: 78%
“…31 Smoking status was categorized into three groups: current smoker, former smoker, and never smoker. Frequency of alcohol use was further assessed by questioning the participants about their average frequency (days per week or month) of alcohol drinking during the last year.…”
Section: Health Behavior Factorsmentioning
confidence: 99%
“…The World Mental Health Surveys states that, annually, SI affects 2.0%-2.1% of the general population [25], and up to 15.5% in South Korea [26]. We found that SI was prevalent among 20.5% of subjects with OSA in this population.…”
Section: Discussionmentioning
confidence: 89%